Desiccation and temperature resistance of the larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae): pedestals for invasion success? - Mutamiswa, Reyard; Machekano, Honest; Singano, Charles; Joseph, Virgil; Chidawanyika, Frank; Nyamukondiwa, Casper (Wiley and Royal Entomological Society, 2022)
The larger grain borer, Prostephanus truncatus (Horn) is an invasive insect pest species of global economic concern. It however remains unknown how P. truncatus succeeds under increasing temperatures and desiccation effects associated with projected climate change. Here, we investigated the effects of desiccation and high-temperature stress on physiological fitness of P. truncatus larvae and adults. Specifically, we measured critical thermal maxima, heat knockdown time and water loss rates following heat and desiccation acclimation. Results showed beneficial heat acclimation effects on heat tolerance (critical thermal maxima and heat knockdown time). Similarly, desiccation acclimation significantly improved both heat tolerance traits, indicating cross-tolerance effects, not for heat knockdown time in larvae. In all cases, adults exhibited more improved heat tolerance than larvae. Conversely, heat acclimation increased water loss rates, and more so in larvae than adults. Improved heat tolerance plus abiotic stress cross-tolerance of P. truncatus may explain its enhanced physiological and ecological fitness in dry tropical and changing climate environments. These results are important in explaining the role of physiology in insect invasions and may inform pest management and forecasting.